PENGEMBANGAN MEDIA LEVIDIO STORYBOARD DALAM PEMBELAJARAN MENULIS TEKS ULASAN FILM/DRAMA PADA SISWA KELAS XI SMK - Kastiyawan, M. Agus; Hudiyono, Yusak; Ahmad, M. Rusydi (Fakultas Ilmu Budaya, Universitas Mulawarman, 2017)
The research that will be raised is about the development of learning media Levidio Storyboard in learning to write the text of film / drama review on the students of class XI SMK. The purpose of this research is (1) Levidio Storyboard learning media in learning to write movie/drama review text, and (2) implementation of Levidio Storyboard media development in learning to write movie/drama review text. This writing is a development writing that refers to the development model of Borg and Gall that has been modified by the author includes seven steps namely writing and gathering information, planning stage, product development stage with Levidio Storyboard, expert validation, first phase revision, field trials, and revisions Final stage improvement. The location of the research was SMKN 7 Samarinda in April s.d. May 2017. Based on data analysis, Levidio Storyboard media is feasible and appropriate for use in learning to write text of film/drama review for students of class XI SMK.Keywords: learning media, levidio storyboard, writing, review text